Effects of land use on processes governing water quality in urbanizing catchments: A case study in the Liangjiang New Area, China. Issue 1 (August 2020) - Luo, Kun; Wu, Conglin; Zheng, HeZhen; Hu, Xuebin; He, Qiang; Shao, Junrong
Abstract: Understanding the effects of land use on processes governing water quality is important for watershed planning and management. This study evaluated the difference in pollution factors due to land use in Liangjiang New Area. Water samples were collected in April (dry season) and September (wet season) of 2014 and 2015 at 20 subcatchments. According to the similarity in land use compositions, cluster analysis divided subcatchments into four land use groups, representing different urbanization levels. The factor analysis identified five pollution factors which explained more than 80% of the variance in data, and revealed nutrients pollutions, anaerobic conditions, soil erosion, effects of eutrophication and oxygen consumption in the rivers, respectively. Using the analysis of principal component scores, we found that the magnitudes of pollution factors were significantly different among the land use groups. Moreover, urban land use had a significantly positive relationship with pollution factors, whereas forest land and farmland displayed opposite effects.